Factors Affecting Supply Chain Performance of Grocery Store in Ende Regency Nusa Tenggara Timur Province - Lubalu, Anthonia; Sutapa, I Nyoman (Proceedings International Conference on Education Innovation and Social Science, 2022)
The article discusses the factors that affect the performance of the supply chain of a grocery store business of Micro Small and Medium Enterprises (MSMEs) in Ende Regency, Nusa Tenggara Timur province. Poorly designed supply chain performance can pose a variety of problems. This is characterized by the stock of goods that are often empty in the warehouse resulting in customers having to look elsewhere. The goal is to get accurate information directly in the field in order to be able to do improvisation in running a business. In addition, the purpose of this study is to find out what factors can affect either directly or indirectly on supply chain performance. The research method is ethnographic method, this method is a writing that describes a society, group or human life. The process of retrieving data on this method uses in-person interviews with sources or customers at a grocery store business in Ende Regency. The results showed that the performance of this supply chain can be improved with several things, including the environment, availability of goods, completeness, service and response of sellers, leather offered and price offers.